Process capability analysis at Chaudry textiles (Malaysia) Sdn Bhd - Mohamed Sallehsu, Kamaruzaman (2008)
Process capability analysis ensures that processes are fit for industry company specification while reduce the process variation and important in achieving product quality characteristic. Its indices are to measure the inherent variability of a process and thus to reflect its performance. The main objective for this research are to predict current and future capability of the process to produce product within specification in the company and to investigate the product produced by the company meet the customer’s specification. This project focuses on Process Capability Analysis that had been applied in small and medium industry in the organization which includes select critical parameters, data collection, study on process capability and data evaluation. This project was successfully done by implementing and applying the capability study to the company.